Access Control in Weakly Consistent Systems - Costa, Tiago Miguel Ferreira da (2018)
Eventually consistent models have become popular in the last years in data storage systems for cloud environments, allowing to give users better availability and lower latency. In this model, it is possible for replicas to be temporarily inconsistent, having been proposed various solutions to deal with this inconsistency and ensure the final convergence of data. However, defining and enforcing access control policies under this model is still an open challenge. The implementation of access control policies for these systems raises it’s own challenges, given the information about the permissions is itself kept in a weakly consistent form. In this dissertation, a solution for this problem is proposed, that allows to prevent the non authorized access and modification of data. The proposed solution allows concurrent modifications on the security policies, ensuring their convergence when they are used to verify and enforce access control the associated data. In this dissertation we present an evaluation of the proposed model, showing the solution respects the correct functioning over possible challenging situations, also discussing its application on scenarios that feature peer-to-peer communication between clients and additional replicas on the clients, with the goal of providing a lower latency and reduce the load on centralized components.